Building ACP capacity to provide information for S&T decision making - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
In February 2004 CTA launched a new initiative that aims to build the national capacities in ACP countries to undertake analyses of agricultural, science, technology and innovation (ASTI) systems and to provide sound information to enhance S&T decision ma